RENAL FAILURE AND UROLOGICAL ASPECTS - Mo’minov M.Sh, (TADQIQOTLAR, 2026)
Abstract:  Renal  Failure  and  Urological  Aspects  Renal  failure  is  a pathological syndrome characterized by a decline in kidney function. It manifests as a sudden  and  significant  reduction  or  complete  cessation  of  the  kidneys’  primary functions—secretory, excretory, and filtration. The disease may occur in two forms: acute  renal  failure,  which  develops  abruptly,  and  chronic  renal  failure,  which progresses gradually. This scientific work examines the role of urological factors in the development of renal failure and their significance in treatment strategies. In addition, the  social  and  clinical  relevance  of  the  disease  and  its  association  with  urological disorders are analyzed. Preventive measures aimed at reducing the risk of renal failure are also considered to be of particular importance. These measures include lifestyle modifications,  hygienic practices,  and pharmacological  prevention  strategies, all  of which are recommended based on scientific evidence.